The Influence of Digital Capabilities on The Performance of Supply Chain Innovation Through Digital Innovation in Manufacturing Companies in Bogor, Indonesia - Anggraeni, Laurensia Puspita; Santosa, Wahyuningsih (Manunggal Halim Jaya, 2025)
In an increasingly digital era, companies must adapt quickly to remain competitive in a competitive global market. Digital capability, which is the organization's ability to utilize digital technology in all aspects of its operations, is the main key in achieving competitive advantage. This study aims to analyze the effect of digital capability on supply chain innovation performance through digital innovation in manufacturing companies in Bogor. The method used is a quantitative approach with a survey using a questionnaire evaluated by a panel of experts. Data were collected from 140 respondents of manufacturing companies in Bogor and analyzed using Structural Equation Modeling (SEM) with AMOS software. The results showed that digital capability has no significant influence on supply chain innovation performance (p-value 0.380 > 0.05). Meanwhile, digital capability has a significant positive influence on digital innovation (p-value 0.033 < 0.05). On the other hand, digital innovation has no significant impact on supply chain innovation performance (p-value 0.484 > 0.05), and digital capability also has no significant effect on supply chain innovation performance through digital innovation based on the mediation flow of direct and indirect (p-value 0.421 > 0.05). The conclusion of this study is that although digital capability can drive digital innovation, it does not necessarily improve supply chain innovation performance directly. Suggestions for future research are to involve more companies from various locations and use mixed quantitative-qualitative research methods to increase validity and in-depth understanding. In addition, there is a need to explore other factors that may affect supply chain innovation performance to strengthen digital capability and digital innovation strategies in manufacturing companies.